Antibacterial mechanisms of thyme essential oil nanoemulsions against Escherichia coli O157:H7 and Staphylococcus aureus: Alterations in membrane compositions and characteristics. (January 2022) - He, Qiao; Zhang, Lianjiao; Yang, Zhehao; Ding, Tian; Ye, Xingqian; Liu, Donghong; Guo, Mingming
Abstract: In this study, the antibacterial activities of thyme essential oil nanoemulsions (TEON) prepared by ultrasonication (US) and high-pressure homogenization (HPH) were evaluated via minimum inhibitory concentration (MIC), minimum bactericidal concentration (MBC), and time-killing curve analyses. TEON-US presented superior bacteriostatic and bactericidal effects, which was found to be correlated with its better physicochemical characteristics (including smaller droplet size and higher zeta potential) compared to TEON-HPH. The underlying antibacterial mechanisms were specifically investigated targeting cell membranes of Escherichia coli O157:H7 (Gram-negative bacterium) and Staphylococcus aureus (Gram-positive bacterium). Thereinto, membrane disintegrations were observed followed by massive leakage of cytoplasmic inclusions. Furthermore, the membrane dysfunctions (involving membrane potential depolarization and fluidity reduction) were likely associated with the modifications seen in the fatty acid composition upon TEONs exposure, and ultimately causing bacterial death. These results deciphered the mode of antibacterial action of TEONs, providing a critical theoretical basis for their future application in food matrix. Highlights: TEON-US possessed a particle size below 10 nm and a zeta potential above 60 mV. TEON-US had lower MIC and MBC values against E. coli and S. aureus than TEON-HPH. TEON-US was stable with particle size remained at nano-scale over 15-days storage. TEONs induced bacterial membrane fluidity reduction and potential depolarization. TEONs may cause compositional and conformational changes in membrane lipids.